2019
DOI: 10.3329/bpj.v22i1.40023
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of Momordica charantia Linn. (Bitter Melon) with Antihyperglycemic Agent Gives Increased Antioxidative and Hepatoprotective Actions in Alloxan-induced Diabetic Rats

Abstract: Bitter melon, a popular vegetable of the Asian and African community, is used as an antidiabetic herb for the management of diabetes and its associated complications. The fastest growing metabolic disorder, diabetes mellitus (DM), is now a major cause of morbidity and mortality in developed countries. All the associated complications produced in diabetes are mainly caused by the imbalance between generation of free radicals and the antioxidant systems like catalase (CAT) and super oxide dismutase (SOD) enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Corresponding author: Mamunur Rashid; Phone: +8801727144582; Email: mamun69jp@yahoo.com DOI: https://doi.org/10.3329/bpj.v23i1. 48327 It is reported that generation of free radicals due to oxidative stress are responsible for the disease complications (Garg et al, 1996;Islam et. al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding author: Mamunur Rashid; Phone: +8801727144582; Email: mamun69jp@yahoo.com DOI: https://doi.org/10.3329/bpj.v23i1. 48327 It is reported that generation of free radicals due to oxidative stress are responsible for the disease complications (Garg et al, 1996;Islam et. al., 2019).…”
Section: Introductionmentioning
confidence: 99%